PENDIDIKAN KARAKTER DALAM PERSPEKTIF AL-QUR'AN: KAJIAN TEMATIK Q.S AL LUQMAN AYAT 13-17 SEBAGAI LANDASAN KURIKULUM - Ishlah Seillariski (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
Character education itself can be implemented through acculturation, habituation, role models, and processes in the community, family, and school environment. Through a holistic approach, it is hoped that character education will be able to create students who care about others, are responsible, and form a young generation with integrity, so that they can make a positive contribution to the country or nation. The purpose of this writing is to provide analytical results related to character education in the perspective of the Qur'an: Thematic Study of Q.S Al Luqman verses 13-17 as the basis for the curriculum. The writing method used in writing this journal is to use a qualitative type. The results obtained from character education in Islam are based on the Qur'an. Character education is a step taken in instilling several good traits so that children become civilized individuals, have Qur'anic characters, and stay away from bad deeds. The conclusion drawn is that character education in the perspective of the Qur'an in Q.S Al Luqman verses 13-17 as the basis of the curriculum has several contents of the Qur'an including awareness of responsibility, justice and wisdom, teachings of goodness, respect for parents, obedience to Allah, and implementation related to monotheism education, worship, and da'wah